The role of primary cilia in the development and disease of the retina - Wheway, Gabrielle; Parry, David A; Johnson, Colin A (Organogenesis, 2014)
The normal development and function of photoreceptors is essential for eye health and visual acuity in vertebrates. Mutations in genes encoding proteins involved in photoreceptor development and function are associated with a suite of inherited retinal dystrophies, often as part of complex multi-organ syndromic conditions. In this review, we focus on the role of the photoreceptor outer segment, a highly modified and specialized primary cilium, in retinal health and disease. We discuss the many defects in the structure and function of the photoreceptor primary cilium that can cause a class of inherited conditions known as ciliopathies, often characterized by retinal dystrophy and degeneration, and highlight the recent insights into disease mechanisms.